Faktor-Faktor yang Mempengaruhi Kebijakan Deviden: Investigasi Pengaruh Teori Stakeholder - Atika Jauhari Hatta (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2002)
Some debates have been considerable around how dividend policy affects shareholder wealth. There are three contradictive theories; some researchers believe that dividends increase shareholder wealth while others argue that dividends are irrelevant, and the others believe that dividend decrease shareholder wealth. The objective of this paper is to investigate the relationship the dividend policy decisions and investments decisions of a firm. The theory has been proposed that can link the two decisions, called stakeholder theory. This theory views the firm as a nexus of contracts and includes investor and non-investor as firm’s stakeholders. The interest of non-investor stakeholder can influence financial decisions through implicit claims. Using net organizational capital (NOC) as a proxy for the level of non-investor stakeholder influences, this research found that such relationship does exist, even though the sign doesn’t consistent with the hypothesis.Keywords: Dividend policy, implicit claim, and Stakeholder theory.